Determinan Profitabilitas terhadap Bank Konvesional di Indonesia - Pamungkas, Wihandaru Sotya; Silveyra, Eka Noviani (Universitas Muhammadiyah Metro, 2023)
The motivation for conducting this research was because, at the beginning of 2020, there was a Covid-19 pandemic which affected the global economy. The research objective is to find the effect of income diversification (RDV), non-performing loans (NPL), and company size (FSZ) on profitability (PRF) in conventional banks. This research uses a sample of conventional banks registered with the Financial Services Authority (OJK) for 2018-2021. The sampling technique used purposive sampling. The number of samples used was 92 banks. Data is obtained through the OJK website and each company. The analytical tool for testing the hypothesis is panel data regression analysis. The results obtained by RDV did not affect PRF, while NPL had a significant negative effect and FSZ had a significant positive effect.